PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING PADA KEMAMPUAN BERCERITA UNTUK MENINGKATKAN KETERAMPILAN SOSIAL PESERTA DIDIK SMP - Ajeng Fernanda Rosmayanti; Anas Ahmadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to understand the discovery learning model on the ability to tell stories to improve the social skills of junior high school students. The method used is classroom research (CAR), in this research carried out in two cycles with each cycle having four stages, namely planning, action, observation and reflection. The subjects of this research were students at junior high school level. Then descriptive data analysis was carried out. The results of the research show an increase in cycle I and cycle II. It can be observed that there is a quite significant increase. In cycle I the average score of all class IX students at SMPN 33 Surabaya was 62.22. So, it can be seen that there is an increase in the average score of class IX students at SMPN 33 Surabaya from cycle I to cycle II, amounting to 11.78%. Social skills also get a boost. This is demonstrated by the results of the pretest and posttest which have been carried out with three indicators, namely self-management skills, academic abilities and compliance skills.